2019
DOI: 10.12659/msm.916948
|View full text |Cite
|
Sign up to set email alerts
|

Novel Multiple miRNA-Based Signatures for Predicting Overall Survival and Recurrence-Free Survival of Colorectal Cancer Patients

Abstract: BackgroundColorectal cancer (CRC) has become a heavy health burden around the world, accounting for about 10% of newly diagnosed cancer cases. In the present study, we aimed to establish the miRNA-based prediction signature to assess the prognosis of CRC patients.Material/MethodsA total of 451 CRC patients’ expression profiles and clinical information were download from the TCGA database. LASSO Cox regression was conducted to construct the overall survival (OS)- and recurrence-free survival (RFS)-associated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 30 publications
1
2
0
Order By: Relevance
“…Because of this feature, in silico tools can predict thousands of miRNA-regulated genes. Recently, studies have found that hsa-miR-891a and hsa-miR-891b can be used as prognostic biomarker and therapeutic target in different types of cancer such as lung cancer [31], breast cancer [32], colorectal cancer [33], and gastrointestinal stromal tumor [34]. In concordance with the present study, hsa-miR891a-3p, osa-miR1858a, and osa-miR1858b were also predicted to have another 645 and 720 targets genes, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…Because of this feature, in silico tools can predict thousands of miRNA-regulated genes. Recently, studies have found that hsa-miR-891a and hsa-miR-891b can be used as prognostic biomarker and therapeutic target in different types of cancer such as lung cancer [31], breast cancer [32], colorectal cancer [33], and gastrointestinal stromal tumor [34]. In concordance with the present study, hsa-miR891a-3p, osa-miR1858a, and osa-miR1858b were also predicted to have another 645 and 720 targets genes, respectively.…”
Section: Discussionsupporting
confidence: 89%
“…X Xu et al, (2019) which could be used to predict the survival of patients. Qian et al, (2019) constructed two prediction models based on miRNAs identified in colorectal cancer patients, the prediction from which were in good agreement with the patients' OS and recurrence-free survival (RFS). Our study identified 40 DE miRNAs in LUAD patients that were associated with m7G, including 34 upregulated and 6 downregulated.…”
Section: Discussionmentioning
confidence: 97%
“…Xie et al (2018) established a four-miRNA signature that correlated with the survival of patients with clear cell renal cell carcinoma. Qian et al (2019) constructed two novel miRNA-based prediction signatures of OS and recurrence-free survival (RFS), which were reliable tools to assess the prognosis of colorectal cancer patients. In addition, Xue et al (2021) screened two independent miRNA datasets acquired from TCGA-ESCA and GSE13937 and revealed that hsa-miR-186-5p and hsa-let-7d-5p could be used as independent prognostic biomarkers for esophageal adenocarcinoma (EADC) and esophageal squamous cell carcinoma (ESCC), respectively.…”
Section: Discussionmentioning
confidence: 99%